Utilization of Social Media Platforms on the Organization of Sports - Abdulraheem Yinusa Owolabi (Indonesian Journal of Sport Management, 2022)
This study investigated utilization of social media platform on organization of sports in North-central zone, Nigeria. Descriptive research design of survey type was used for this study. The population for this study comprises of officials of sports council in the study area. Purposive, stratified and random sampling technique were used to select 806 respondents. Researcher structured questionnaire was used for the study. The instrument was validated by lecturers in the Department of Human Kinetics Education. The reliability level of the instrument was established through test re-test method using Pearson Product Moment Correlation PPMC with 0.86r result. The administration of instrument was done by the researcher and three (3) trained research assistants. The data collected were analysed using Pearson Product Moment Correlation to test the hypotheses formulated for the study at 0.05 alpha level. The result revealed that digital media are effective to organization of sports, uses of blog and microblogs play a vital role in the organization of sports. The study recommends that the management staff, coaches, association secretaries and clerks of the state sports council in the North Central zone should be encouraged to acquire skills in the use of mobile application tools for their administrative operations.